2016
DOI: 10.1002/ptr.5699
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of a Proprietary Glycyrrhizin Product during Alcohol Consumption: A Randomized, Double‐Blind, Placebo‐Controlled, Crossover Study

Abstract: Traditionally, licorice has been used to treat liver problems. Glycyrrhizin, the primary active compound, has been shown to suppress elevations in liver enzymes that occur when the liver becomes diseased or damaged. This randomized, double-blind, placebo-controlled, crossover study evaluated the hepatoprotective effects of a proprietary glycyrrhizin product during alcohol consumption. Twelve healthy individuals (six male and six female subjects) in a clinic setting consumed vodka nightly for 12 days with the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…F I G U R E 1 (a and b) Trythema, bullae, crusts, and hyperpigmentations on the dorsum of hand and neck. (c and d) The same patient was treated with glycyrrhizin for 1 month Glycyrrhizin is a potent hepatoprotective constituent extracted from the traditional Chinese medicine liquorice, and is clinically used for treating chronic liver diseases in Asian countries (Chigurupati et al, 2016). Our patient had a history of having continuously ingested alcohol for 30 years before the onset of disease.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…F I G U R E 1 (a and b) Trythema, bullae, crusts, and hyperpigmentations on the dorsum of hand and neck. (c and d) The same patient was treated with glycyrrhizin for 1 month Glycyrrhizin is a potent hepatoprotective constituent extracted from the traditional Chinese medicine liquorice, and is clinically used for treating chronic liver diseases in Asian countries (Chigurupati et al, 2016). Our patient had a history of having continuously ingested alcohol for 30 years before the onset of disease.…”
Section: Discussionmentioning
confidence: 89%
“…Emerging evidence demonstrated that glycyrrhizin acted as an antioxidant inhibiting reactive oxygen species formation and inhibit secretion of cytokines such as TNF-α, IL-1, and IL-6 (Ishida et al, 2012). Recently, the hepatoprotective effects of glycyrrhizin during alcohol consumption have been confirmed in a randomized, double-blind, and placebo-controlled study (Chigurupati et al, 2016). Consistently, in our case, glycyrrhizin downregulated the levels of liver enzymes and PCT severity, suggesting that elevated levels of liver enzymes GGT, AST and ALT not only predict the status of liver damage but also directly reflect the severity of PCT.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizin is a potent hepatoprotective constituent extracted from the traditional Chinese medicine liquorice, and is clinically used for treating chronic liver diseases in Asian countries. Moreover, glycyrrhizin has exhibited immune‐modulatory effects in vivo and in vitro 3 . Combination therapies may enhance efficacy and avoid adverse events, therefore, we speculated that glycyrrhizin would be a proper candidate in combination therapy of GPP patients with LTA.…”
Section: Introductionmentioning
confidence: 99%
“…G. glabra and its bioactive compounds have antioxidant (Sil and Chakraborti, ), antiviral (Nassiri Asl and Hosseinzadeh, ), antimicrobial, antiprotozoal, antiinflammatory, and immunomodulatory activities (Nassiri Asl and Hosseinzadeh, ). They could reverse drug resistance of methicillin‐resistant Staphylococcus aureus infections (Gaur et al ., ) and evoke hepatoprotective (Chigurupati et al ., ; Nassiri Asl and Hosseinzadeh, ) and antitumor effects (Nassiri Asl and Hosseinzadeh, ). Besides, they could be used as a remedy in cardiovascular diseases and diabetes owing to their antiplatelet aggregation activity, thrombin inhibitory effects, vasorelaxant effects, antiangiogenic properties, and positive effects on peroxisome proliferator‐activated receptor ɤ (PPARɤ) (Nassiri Asl and Hosseinzadeh, ; Hosseinzadeh and Nassiri Asl, ).…”
Section: Introductionmentioning
confidence: 99%